PENGARUH PENERAPAN MODEL PEMBELAJARAN ARTIKULASI DIAWALI DENGAN PENDEKATAN KONTSRUKTIVISME TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XII SMKN 2 GUNUNG TALANG KABUPATEN SOLOK TAHUN PELAJARAN 2013/2014 - Sari, Riri Permata; Zulfaneti, Zulfaneti; Cesaria, Anna (Pendidikan Matematika, 2013)
This research was based by the understanding of mathematical concept and students are less able to express the idea with creatively and scientifically. This research aim to determine whether studentsâ understanding of mathematical concept by applying learning models of articulation beginning with constructivism approach is better than the studentsâ understanding of mathematical concept with the application of conventional learning at class twelve grade students of SMKN 2 Gunung Talang Kabupaten Solok School-Year 2013/2014. Type of research is experimental research. Population of research are students at twelve grade SMKN 2 Gunung Talang School-Year 2013/2014. The sampling technique is done randomly whith Â class XII Akuntansi was chosen ekperimental class and class Marketing was control class. The instrument used in this study was final test with indicator of understanding the mathematical concept. Form of test used is a form of essay to amount seven question with a reliability test . Hypothesis testing used a t-test. The results of the data analysis obtained from Â and Â , it can be concluded that the studentsâ understanding of mathematical concept with application of learning models of artikulasi beginning whith constructivism aproach was better than the students understanding of mathematical concept with conventional learning at twelve grade students SMKN 2 Gunung Talang Kabupaten Solok School-Year 2013/2014.